Death note : Give-and-take / 6 - Oba, Tsugumi (Deathnote, 2008)
"Although they've collected plenty of evidence tying the seven Yotsuba members to the newest Kira, Light, L and the rest of the taskforce are no closer to discovering which one actually possesses the Death Note. Desparate for some headway, L recruits Misa to infiltrate the group and feed them information calculated to bring Kira into the open."